HUBUNGAN PENGETAHUAN DENGAN STIGMA MASYARAKAT PADA PASIEN COVID-19 DI KOTA TANGERANG - Reza Rizki Septian (Nusantara Hasana Journal, 2022)
In early 2020, the word was caught off guard by the outbreak of unknown pneumonia that began  in Wuhan, Hubei Province. It spread rapidly throughout more than 190 countries and territories. This outbreak is named coronavirus disease 2019 (COVID-19), caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Research objectives  to find out whether there is a correlation of the knowledge of  people’s stigma with patients Covid-19 in Kota Tangerang. This research uses descriptive analytical research with are search design cross sectional. The sampling technique used in this study is random sampling by using a questionnaire, the total population is 25.158 using a random sampling technique with the Slovin formula, the results obtained are 100 respondents consisting of local residents. Obtained, based on the chi square test of Sig. 0.000 (p <0.05), it can be concluded that Ho is accepted and Ha is rejected. Thus, it can be interpreted that there is a significant relationship between the level of knowledge and people’s stigma with patients Covid-19 in Kota Tangerang.